Impact of emotion regulation on emotional experiences following social rejection: an ERP study - Xie, Dengfeng; Lu, Jiamei; Xie, Zhangming (Frontiers in Psychology, 2025)
Social rejection elicits potent emotional responses with significant mental health implications. This event-related potential (ERP) study characterized the neurochronometry of emotion regulation during social rejection. Key findings revealed that (1) linear mixed-effects modeling confirmed attention transfer significantly reduced late positive potential (LPP) amplitudes versus cognitive reappraisal and non-regulation across all time windows; (2) the superiority of attention transfer was most pronounced during the early/mid-processing stages, achieving rapid disengagement from rejection stimuli; (3) enhanced suppression under social rejection reflected context-dependent regulatory dynamics. Attention transfer demonstrates contextually optimized efficacy for rapid threat disengagement during social rejection. However, EEG source localization limitations preclude definitive conclusions regarding dorsolateral prefrontal cortex (DLPFC) engagement; future studies should employ multimodal approaches (e.g., fMRI-EEG) to verify neuroanatomical mechanisms.